Comorbidity between Type 2 Diabetes and Depression in the Adult Population: Directions of the Association and Its Possible Pathophysiological Mechanisms - Line Iden Berge; Trond Riise (International Journal of Endocrinology)
Type 2 diabetes and depression are regarded as comorbid conditions, and three possible directions of the association between the diseases can underlie this observation of comorbidity. First, common etiology can increase a person’s risk of both diseases; second, persons with type 2 diabetes have increased prevalence or risk of future development of depression; or third, persons with depression have increased prevalence or risk of development of type 2 diabetes. This review gives an overview over possible pathophysiological mechanisms for each of the directions of the association between type 2 diabetes and depression and further discusses epigenetics as an additional, direction independent approach. We argue that unspecific pathophysiological mechanisms involved in the stress response might, at least to some extent, explain each of the directions of the association between type 2 diabetes and depression, while changes in brain structure and function among persons with diabetes and possible increased risk of development of type 2 diabetes after use of antidepressant agents could represent more disease specific mechanisms underlying the comorbidity.